Effect of adsorbed magnesium on soil hydraulic conductivity - Liu, Chun-lanng; Brand, E.W.; Petersen, J. L.; Moh, Za-Chieh; Okamoto, Masami; Paiboon Prabhudham; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1975)
This research was conducted to find the effect of adsorbed magnesium on the soil hydraulic conductivity, and the main concern is the effect of adsorbed magnesium plus adsorbed sodium on hydraulic conductivity. Sixteen columns of a soil from central Thailand were prepared in the laboratory by leaching them with a laboratory preparation of 300 meq./litre electrolyte concentration salt solutions. The salt solutions were made from sodium chloride, calcium chloride and magnesium chloride in different proportions, The hydraulic conductivities were then measured by applying a fixed head of 5 meq, /litre salt solutions. The experimental results indicated that adsorbed calcium improved the soil hydraulic conductivity, while adsorbed sodium reduced it. The soil with adsorbed magnesium alone had a lower conductivity than the calcium soil but higher than where sodium was absorbed alone. In the presence of sodium, however, adsorbed magnesium had a detrimental effect on the soil hydraulic conductivity. If the concentration of absorbed magnesium was 40% or more, the hydraulic conductivity was greatly decreased by the presence of 10% or more adsorbed sodium.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science at the Asian Institute of Technology, Bangkok, Thailand .
Thesis (M.Sc.) - Asian Institute of Technology, 1975
Keywords: Soil permeability; Soil moisture; Soil mechanics